Expression of macrophage migration inhibitory factor in diffuse systemic sclerosis. Issue 5 (1st May 2003) - Selvi, E; Tripodi, S A; Catenaccio, M; Lorenzini, S; Chindamo, D; Manganelli, S; Romagnoli, R; Ietta, F; Paulesu, L; Miracco, C; Cintorino, M; Marcolongo, R
Abstract : Objective: To evaluate whether, in patients with the diffuse form of systemic sclerosis (dSSc), macrophage migration inhibitory factor (MIF) production is dysregulated. Methods: 10 patients with dSSc and 10 healthy controls, matched for age and sex, were studied. MIF expression was evaluated by immunohistochemistry on formalin fixed skin biopsies of patients with dSSc and controls. MIF levels were assayed in the sera and in the supernatants of skin cultured fibroblasts by a colorimetric sandwich enzyme linked immunosorbent assay (ELISA). MIF concentrations in culture medium samples and in serum samples were compared by Student's two tailed t test for unpaired data. Results: Anti-MIF antibody immunostained the basal and mainly suprabasal keratinocytes. Small perivascular clusters of infiltrating mononuclear cells were positive; scattered spindle fibroblast-like cells were immunostained in superficial and deep dermal layers. The serum concentrations of MIF in patients with dSSc (mean (SD) 10705.6 (9311) pg/ml) were significantly higher than in controls (2157.5 (1288.6) pg/ml; p=0.011); MIF levels from dSSc fibroblast cultures (mean (SD) 1.74 (0.16) ng/2×10 5 cells) were also significantly higher than in controls (0.6 (0.2) ng/2×10 5 cells; p=0.008). Conclusion: These results suggest that MIF may be involved in the amplifying proinflammatory loop leading to scleroderma tissue remodelling.